Process writing as reading comprehension tool for expository text in social studies - Alcazar, Marie Yvette Concepcion (2006)
Using a counterbalanced experimental approach, the study reported herein determined if process writing has a significant effect on 2nd graders' comprehension of Social Studies expository text. Results show that after undergoing process writing activities, the students' reading comprehension improved, and after writing incorporated new knowledge with background knowledge, and demonstrated multi-level comprehension.
Keywords: Reading comprehension -- Study and teaching (Elementary)